EFFECT OF ESTRADIOL LEVELS ON PREGNANCY OUTCOME IN OBESE WOMEN - Rehman, Rehana; Hussain, Zahir; Faraz, Naveed (Journal of Ayub Medical College Abbottabad, 2012)
Background: The incidence of obesity in women of reproductive age group has encountered problems of infertility with frequent referral to reproductive clinics. In order to know whether increase in body mass index (BMI) is associated with poor reproductive outcome, current study was aimed to relate women’s BMI, estradiol (E2) levels, and clinic pregnancy rates after intra cytoplasmic sperm injection (ICSI). Methods: Quasi experimental design of 323 women was conducted from June 2010 till August 2011. Women were grouped on the basis of BMI; Group A, BMI <18 (underweight); Group B, BMI 18-22.9 (normal weight); Group C, BMI 23-25.9 (overweight); and Group D, BMI ‰¥26 (obese). Procedure of ICSI commenced by down regulation of ovaries followed by controlled ovarian stimulation. Oocyte pickup was done 36 hours after ovulation induction by hCG, eggs fertilised in vitro were graded and only blastocysts were transferred. Serum samples of basal E2, peak E2 (day of hCG administration) and mid-luteal E2 (7 days after egg collection) measured by ELISA were compared in all BMI groups. Pregnancy outcome of these was categorised as: no conception Î²-hCG <5 mIU/ml, preclinical abortion with Î²-hCG >5 mIU/ml, no cardiac activity on transvaginal scan (TVS) and clinical pregnancy with Î²-hCG >5 mIU/ml and cardiac activity on trans-vaginal scan. Results: Obese women with BMI ‰¥26 had lowest basal, peak and mid-luteal E2 with minimum clinical pregnancy rates compared to rest of the groups. Conclusion: A high BMI is associated with decreased E2 levels in all phases of ovarian cycle and has a negative impact on pregnancy outcome. Keywords: Intra-cytoplasmic sperm injection, Body mass Index, Estradiol, Obesity, Infertility